Embracing Google Translate: EFL Students’ Attitudes on Enhancing Literacy Practice - Delfitha Lia; Novalita Fransisca Tungka (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2023)
This study investigates students' attitudes toward the use of Google Translate (GT) in their online literacy practices. The study looks at the results of an online questionnaire survey completed by 70 students studying English Language Education at Universitas Sintuwu Maroso in Poso, Central Sulawesi. The purpose of this research is to examine how students' attitudes regarding GT manifest themselves in their reading practices, taking into account behavioral, cognitive, and affective components. The results showed that: First, from a behavioral standpoint, students consistently show a proclivity to actively use GT for various translation tasks, ranging from solitary words to complete paragraphs, essays, or articles; Second, students have differing cognitive attitudes about the ethical implications of GT use, with some viewing it as a sort of cheating depending on the context; Finally, on an affective level, students tend to accept the usage of GT as normal, enjoy using it, and may even become dependent on its features. This study gives insight on the complexities of students' attitudes toward GT and how these beliefs influence their literacy practices. Educators can better appreciate the obstacles and opportunities that come with the incorporation of GT in online language learning environments by understanding the behavioral, cognitive, and affective elements. This knowledge can be used to design successful educational practices that take advantage of GT's benefits while addressing its possible limitations in order to improve students' overall language ability.